Study of Al-Qur’an Verses about the Value of Religious Moderation in Islamic Education Textbooks in Muhammadiyah and Nahdlatul Ulama Elementary Schools - Harimurti, Shubhi Mahmashony; Hilmi, Irfan; Makruf, Syahdara Anisa; Suwarno, Rahmadi Wibowo (Fakultas Studi Islam dan Peradaban, Universitas Muhammadiyah Yogyakarta, 2026)
Nahdlatul Ulama (NU) and Muhammadiyah, as pioneers of religious moderation in Indonesia, have a significant influence on education through the development of Islamic Education (PAI) textbooks. The study of the Qur'anic verse used to strengthen the value of religious moderation in PAI textbooks is important, given the diversity of views on the concept of wasathiyah, differences in references, and variations in implementation. The problem of this research is, first, the similarities and differences in the perspectives of NU and Muhammadiyah on determining which Qur'anic verses serve as the basis for religious moderation in PAI textbooks and their application. This research aims to analyze and synthesize studies of Qur'anic verses that serve as the basis for religious moderation in the PAI textbooks of the NU and Muhammadiyah. This research uses a field method with a qualitative approach. The results showed that NU and Muhammadiyah have common ground in making QS: al-Kafirun verse 6 and QS. Al-Hujurat verse 13 is the main reference in developing the value of religious moderation. Students in both the school environment and everyday life can internalize the application of these verses. This finding underscores the importance of inter-organizational collaboration in compiling moderation-based PAI textbooks sourced from the Qur'an. It not only strengthens the nation's harmony and integrity but also increases Indonesian Islamic education's contribution to promoting world peace in the era of disruption.